Tinjauan Literatur: Pemanfaatan Teknologi Augmented Reality sebagai Media Pembelajaran Interaktif Di Tingkat Sekolah Dasar - Rinaldi, Rizky; Fahmi, Khairul; Masyitah, Masyitah (FKIP Universitas Wisnuwardhana, 2024)
This research is a literature review of a series of previous research journals that discuss the utilization of Augmented Reality technology as an interactive learning media at the elementary school level. This research includes an analysis of the models used, an evaluation of the advantages and disadvantages of each model, and an in-depth discussion of the implications and significance of the models that have been reviewed. Based on the literature review conducted on a series of research journals on the utilization of Augmented Reality (AR) technology as an interactive learning media at the elementary school level, several significant conclusions can be drawn. First, the use of AR technology in the context of elementary school learning has been proven effective in improving the learning process by making it more interesting, interactive, and easy to understand for students. However, the implementation of AR technology in learning still faces several challenges, such as limited facilities and teacher readiness in adopting the technology.